eCM 2015
DOI: 10.22203/ecm.v029a16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of orofacial stem cell niches and their innervation through microfluidic devices

Abstract: Stem cell-based mediated therapies represent very promising approaches for tissue regeneration and are already applied with success in clinics. These therapeutic approaches consist of the in vitro manipulation of stem cells and their consequent administration to patients as living and dynamic biological agents. Nevertheless, the deregulation of stem cells function might result in the generation of pathologies such as tumours or accelerated senescence. Moreover, different stem cells sources are needed for regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 85 publications
1
50
0
1
Order By: Relevance
“…Cultures of DMSCs and MSCs are indistinguishable, and at present no markers permit selective identification of either cell type from culture-expanded DMSC populations (Pagella et al, 2015). Likewise, it is not yet known whether DMSC properties reside in distinct cell subpopulations.…”
Section: Stem Cells Within Teethmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultures of DMSCs and MSCs are indistinguishable, and at present no markers permit selective identification of either cell type from culture-expanded DMSC populations (Pagella et al, 2015). Likewise, it is not yet known whether DMSC properties reside in distinct cell subpopulations.…”
Section: Stem Cells Within Teethmentioning
confidence: 99%
“…Despite similar phenotypic characteristics, DMSCs from different locations have significant functional heterogeneity both in vitro and in vivo, thus indicating distinct physiological roles within teeth Pagella et al, 2015). In the dental pulp, DMSCs are located mainly in two niches: the apical niche and the perivascular niche Zhao et al, 2014).…”
Section: Stem Cells Within Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies have demonstrated that mesenchymal stromal/stem cells (MSCs) are suitable to these protocols because of their high expansion ability and differentiation potential both in culture and animal models. MSC-based therapies have already been applied in the clinics and mainly consist of administration of cells, alone, or together with scaffolds, to damaged, or pathological sites (Pagella et al, 2015). Bone marrow (BM), Wharton's jelly and adipose tissue are conventional sources of MSCs, but owing to the easy tooth access and the low morbidity of tooth collection protocols, dental pulp (DP) previously emerged as an valuable source of MSCs for tissue engineering-based therapies (Huang et al, 2009; Harrington et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies of Gronthos et al (2000) demonstrated that undifferentiated DP cells include a small population—less than 5% of cells—that possess phenotypic features of MSCs and are able to form a pulp-dentin complex upon engraftment in vivo in immunodeficient mice (Gronthos et al, 2000). DP-MSCs mostly reside in perivascular stem cell niches that provide cells a highly regulated microenvironment instructing them to remain quiescent and preventing them to proliferate, differentiate, or undergo apoptosis (Moore and Lemischka, 2006; Mitsiadis et al, 2007; Pagella et al, 2015). Perivascular localization of DP-MSCs was ascertained by the fact that a large proportion (more than 60%) of clonogenic DP-MSCs were present in the pericyte fraction and by their expression of specific pericyte and smooth muscle cell markers (Shi and Gronthos, 2003; Alliot-Licht et al, 2005; Lopez-Cazaux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%